ANALYSIS ON READING TEACHING MATERIAL BASED ON CRITICAL READING SKILL AT UIN MALANG | تحليل مادة مهارة القراءة على أساس القراءة الناقدة في جامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج - Laily Fitriani; Amalia Harokah Islamiyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Teaching material has an important role in learning, so in providing good teaching materials, it must refer to the principles of the preparation of good teaching books, one of which is the principle of education. This study aimed to analyze Maharah al-Qiraah 2 material in Arabic and Letters Department base on the principle of education, namely: curriculum, syllabus, and suitability material content, suitability presentation of material and language used. The type research is descriptive qualitative research by content analysis. The result of this research explain from suitability of the content Maharah al-Qiraah 2 material suitable by the curriculum and syllabus in Arabic language and Letters Department that aimed to analyze the discourses in learning material. The suitability of presentation material suitable by the gradation start from easy material to difficult material, but need to choose the argumentative topics and reformulating the argumentative questions in exercises which support students to critical thingking.